2020
DOI: 10.1038/s41598-020-74001-3
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive interleukin-6 blockade in patients with COVID-19

Abstract: Excessive interleukin-6 signaling is a key factor contributing to the cytokine release syndrome implicated in clinical manifestations of COVID-19. Preliminary results suggest that tocilizumab, a humanized monoclonal anti-interleukin-6 receptor antibody, may be beneficial in severely ill patients, but no data are available on earlier stages of disease. An anticipated blockade of interleukin-6 might hypothetically prevent the catastrophic consequences of the overt cytokine storm. We evaluated early-given tociliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 35 publications
0
37
0
1
Order By: Relevance
“…Nevertheless, the inconsistency of the results does not allow any conclusion—mainly due to the very low number of patients [ 71 , 72 ]. Although not always reaching statistical significance, almost all studies showed improvements in survival rate, respiratory functions, reduction in ICU admission, and reduced the need for mechanical ventilation in COVID-19 patients with rather severe symptoms when treated with TCZ in addition to standard of care [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. However, in a randomised, double-blind, placebo-controlled clinical trial, tocilizumab did not show any beneficial effects in terms of mortality rate or preventing intubation in moderately ill, hospitalised COVID-19 patients [ 85 ].…”
Section: Clinical-stage Therapeuticsmentioning
confidence: 99%
“…Nevertheless, the inconsistency of the results does not allow any conclusion—mainly due to the very low number of patients [ 71 , 72 ]. Although not always reaching statistical significance, almost all studies showed improvements in survival rate, respiratory functions, reduction in ICU admission, and reduced the need for mechanical ventilation in COVID-19 patients with rather severe symptoms when treated with TCZ in addition to standard of care [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. However, in a randomised, double-blind, placebo-controlled clinical trial, tocilizumab did not show any beneficial effects in terms of mortality rate or preventing intubation in moderately ill, hospitalised COVID-19 patients [ 85 ].…”
Section: Clinical-stage Therapeuticsmentioning
confidence: 99%
“…), anti-pyretic (paracetamol), anti-histaminic (cetirizine,), antibiotics (cephalosporins), corticosteroids (prednisolone, methylprednisolone), monoclonal antibodies (tocilizumab, imatinib) [16]. In this context, the IL-6 antagonists are considered to have better therapeutic benefits in the symptomatic management of COVID-19, in these lines TCZ is considered as one of the most commonly used medication to suppress the cytokine storm in COVID-19 patients [17]. There are multiple case series, retrospective and prospective studies available on the therapeutic role of TCZ in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted January 29, 2021. ; https://doi.org/10.1101/2021.01.27.21250599 doi: medRxiv preprint IL-6 antagonists are considered to have better therapeutic benefits in the symptomatic management of COVID-19, in these lines TCZ is considered as one of the most commonly used medication to suppress the cytokine storm in COVID-19 patients [17]. There are multiple case series, retrospective and prospective studies available on the therapeutic role of TCZ in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…These studies allowed the refinement of a plausible structural model for the interaction between these two proteins, which we used to perform a second in silico screening of our drug repurposing library. Effective inhibitors of this interaction would enable the selective modulation of virus-induced immune responses, as opposed to the nonspecific effects of currently explored treatment options targeting host immune and inflammatory pathways, such as IL-6 antibodies and steroids [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%